2005
DOI: 10.1002/arch.20076
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pharmacological analysis of an octopamine receptor from american cockroach and fruit fly in response to plant essential oils

Abstract: Octopamine receptors from American cockroach, Periplaneta americana (Pa oa1), and fruit fly, Drosophila melanogaster (OAMB), were cloned and permanently expressed in HEK-293 cells, and found to activate adenylate cyclase activity and increase [Ca2+]i levels through G-protein coupled receptor signaling pathways. Sequencing information (GenBank accession number AY333178) and functional data of Pa oa1 were recently published. Saturation binding analysis with 3H-yohimbine was performed with Pa oa(1) and OAMB expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(130 citation statements)
references
References 23 publications
2
118
1
9
Order By: Relevance
“…It has previously been suggested that octopamine receptor activity is enhanced with the presence of an oxygen atom (13). However, p-cymene, which lacks an oxygen substituent, showed a significant result in our assay, but was not as effective as other monoterpenoids that contained an oxygen substituent.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…It has previously been suggested that octopamine receptor activity is enhanced with the presence of an oxygen atom (13). However, p-cymene, which lacks an oxygen substituent, showed a significant result in our assay, but was not as effective as other monoterpenoids that contained an oxygen substituent.…”
Section: Discussioncontrasting
confidence: 68%
“…Various studies have indicated that monoterpenoids may have several mechanisms of action. Mechanisms that have been reported include: inhibition of acetylcholinesterase (5,6), binding at the GABA receptor (7)(8)(9)(10)(11), binding at the nicotinic acetylcholine receptor (12), the octopamine receptor (13,14), and the tyramine receptor (15). Previous studies have also described quantitative structure-activity relationships (QSARs) to describe the toxicity of monoterpenoids and their interaction at the GABA receptor (11).…”
mentioning
confidence: 99%
“…Está presente en el sistema nervioso de todos los insectos y actúa como neurotransmisor, neurohormona y neuromodulador (147). Otra función que se le atribuye está relacionada con el comportamiento activo o de "atención", por lo que se ha sugerido que forma parte de un sistema general que prepara al insecto para su actividad vigorosa.…”
Section: Mecanismo De Acciónunclassified
“…Algunos autores han planteado que los componentes de los aceites esenciales actúan bloqueando los receptores de la octopamina (131) y produciendo alteraciones neurológicas graves con efectos nocivos para los insectos. El eugenol y el timol, por ejemplo, pueden funcionar mediante el bloqueo de estos receptores (147,148). Con el acoplamiento molecular se ha demostrado que el carvacrol, el eugenol y el eucaliptol son capaces de interactuar en el sitio de unión del receptor oamb de la octopamina de Ae.…”
Section: Mecanismo De Acciónunclassified
“…Thus, grc3 most probably encodes a second tyramine receptor expressed in the locust (Molaei et al, 2005, this issue). The following two reports provide detailed information on the responses of a tyramine receptor from Bombyx mori to 2-phenylethylamines and 5-phenyloxazoles (Ozoe et al, 2005, this issue) and of an octopamine receptor from Periplaneta americana to plant essential oils (Enan, 2005, this issue). These findings are important with respect to the limited knowledge of the pharmacological properties of tyramine and octopamine receptors, which have both been discussed as potential insecticide targets (Roeder et al, 2003).…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 99%